Sex differences in potential triggers of myocardial infarction - Olsson, Anneli; Mohammad, Moman A; Rylance, Rebecca; Platonov, Pyotr G; Sparv, David; Erlinge, David (European heart journal open, 2023)
Abstract Aims Internal and external triggers affect seasonal and circadian variations of myocardial infarction (MI). We aimed to assess sex differences in the common triggers of MI. Methods and results A nationwide, retrospective, cross-sectional postal survey study was conducted. Individuals who experienced a MI during holidays and weekdays were identified through the SWEDEHEART registry. Twenty-seven potential MI triggers were rated in regards to occurring more or less than usual during the last 24 h before the MI. Three areas were covered: activities, emotions, and food or alcohol consumption. A logistic regression model was used to identify sex differences for each trigger and odds ratios (ORs) were reported. Four hundred and fifty-one patients, of whom 317 were men, responded. The most commonly reported triggers were stress (35.3%), worry (26.2%), depression (21.1%), and insomnia (20.0%). Women reported emotional triggers including sadness [OR 3.52, 95% confidence interval (CI) 1.92–6.45], stress (OR 2.38, 95% CI 1.52–3.71), insomnia (OR 2.31, 95% CI 1.39–3.81), and upset (OR 2.69, 95% CI 1.47–4.95) to a greater extent than men. Outdoor activity was less reported by women (OR 0.35, 95% CI 0.14–0.87). No significant sex differences were found in other activities or food and alcohol consumption. Conclusion Self-experienced stress and distress were higher among women prior to MI compared with men. Understanding sex perspectives in acute triggers may help us find preventive strategies and reduce the excess numbers of MI. Graphical Abstract Graphical abstract